Anti-fungal activity of carboxymethyl cellulose (CMC) edible coatings with potassium sorbate in raw pili (Canarium ovatum) kernels - Tabardillo, Joyce Abigail A.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2012)
The study investigated the antifungal activity of carboxymethyl cellulose (CMC) edible coatings with potassium sorbate on raw pili (Canarium ovatum) nuts. Halved pili nuts were coated with varying concentrations of carboxymethyl cellulose (0.75, 1.0, and 1.25 %) and potassium sorbate (0, 0.25, 0.5, and 1.0%). Yeast and mold count (YMC) was obtained from coated and uncoated pili kernels after 24 hours of equilibriation. Antifungal activity of the edible coatings produced was tested against Aspergillus niger using agar diffusion assay. Regression analysis showed that only potassium sorbate had an effect on the yeast and mold count of the samples. A potassium sorbate concentration of at least 0.457% was found to reduce YMC to 5000 cfu/g. Analysis for activity against Aspergillus niger showed that both carboxymethyl cellulose and potassium sorbate affected the zone of inhibition. However, verification of the models deviated from values obtained from the prediction models. Samples with optimum edible coating concentrations were not significantly different from uncoated, control samples in terms of appearance, flavor, and overall acceptability. Acceptability ratings for mouthfeel and aroma were found to be significantly lower in coated samples than in the control. Results show that carboxymethyl cellulose edible coatings with potassium sorbate can protect raw pili nuts from fungal infection.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Pili